THAP1 mutations and dystonia phenotypes: genotype phenotype correlations. - Xiromerisiou, Georgia; Houlden, Henry; Scarmeas, Nikolaos; Stamelou, Maria; Kara, Eleanna; Hardy, John; Lees, Andrew J; Korlipara, Prasad; Limousin, Patricia; Paudel, Reema; Hadjigeorgiou, Georgios M; Bhatia, Kailash P (Mov Disord, 2012)
THAP1 mutations have been shown to be the cause of DYT6. A number of different mutation types and locations in the THAP1 gene have been associated with a range of severity and dystonia phenotypes, but, as yet, it has been difficult to identify clear genotype phenotype patterns. Here, we screened the THAP1 gene in a further series of dystonia cases and evaluated the mutation pathogenicity in this series as well as previously reported mutations to investigate possible phenotype-genotype correlations. THAP1 mutations have been identified throughout the coding region of the gene, with the greatest concentration of variants localized to the THAP1 domain. In the additional cases analyzed here, a further two mutations were found. No obvious, indisputable genotype-phenotype correlation emerged from these data. However, we managed to find a correlation between the pathogenicity of mutations, distribution, and age of onset of dystonia. THAP1 mutations are an important cause of dystonia, but, as yet, no clear genotype-phenotype correlations have been identified. Greater mutation numbers in different populations will be important and mutation-specific functional studies will be essential to identify the pathogenicity of the various THAP1 mutations. © 2012 Movement Disorder Society.
Keywords: Adolescent; Adult; Apoptosis Regulatory Proteins; Databases, Factual; Diagnosis, Computer-Assisted; DNA-Binding Proteins; Dystonia; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Mutation; Nuclear Proteins; Phenotype; Predictive Value of Tests; Survival Analysis; Young Adult